2021
DOI: 10.1101/2021.12.10.21267618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring the impact of COVID-19 vaccination and immunity waning: a modelling study for Portugal

Abstract: Vaccination strategies to control COVID-19 have been ongoing worldwide since the end of 2020. Understanding their possible effect is key to prevent future disease spread. Using a modelling approach, this study intends to measure the impact of the COVID-19 Portuguese vaccination strategy on the effective reproduction number and explore three scenarios for vaccine effectiveness waning. Namely, the no-immunity-loss, 1-year and 3-years of immunity duration scenarios. We adapted an age-structured SEIR deterministic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…With the development of COVID-19 vaccines, policy makers started vaccination campaigns with the aim to protect individuals and relax NPIs. Vaccines became the most important 1 intervention for mitigating disease severity and spread, allowing the return of social and economic activities [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of COVID-19 vaccines, policy makers started vaccination campaigns with the aim to protect individuals and relax NPIs. Vaccines became the most important 1 intervention for mitigating disease severity and spread, allowing the return of social and economic activities [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Again, vaccine hesitancy was modeled population-wide by assuming either a high booster intake (85% to 98%) of individuals 50 years of age or higher with comorbidities, or modeled with a reduced intake of 50%. These models concluded that a high adherence to frequent booster doses is necessary to avoid future outbreaks and prevent a burden on the healthcare system—a conclusion shared by studies using differential equations [ 37 , 38 ]. Since adherence to frequent boosters is the key but it was only modeled by assuming a percentage across wide sub-populations, it is important for future ABMs to address this research gap by detailing how individuals decide to get vaccinated as a function of sociodemographic, health, psychological, and information-related variables.…”
Section: Introductionmentioning
confidence: 99%